To what extent is risk transfer a Governmental tactic to disguise the true cost of the PFI in the Health Sector? A comparison of rates of risk transfer and the breakdowns of those risks in hospital PFI projects using 6% and the 3.5% discount rates. - Pearson, Claire (2007)
It has been suggested by some authors that the justification for using private finance to build NHS hospitals-that it offers VFM by removing risk from the NHS Trusts throughout the life of the projectsis just a Governmental tactic to justify the use of private finance because the alternative public finance is unavailable in the large quantities that is needed (Pollock et al. 2002). The Government have the view that enhanced VFM results from public and private sectors concentrating on what it is perceived that they each do best (Gallimore et al. 1997). The risk measurement and allocation process is, however, fraught with subjectivity and this is where academic criticism lies. Both Pollock et al. (2002)and Froud (2003) said that risk transfer was the deciding factor in hospital PFI economic analyses and without it there would be no justification for PFI. Here, I investigate whether the risk transferred to make the PFI options VFM is a legitimate process or not. This is done by investigating differences between the 3.5% and 6% discount rate hospital PFI projects. Both the net risk transfer and the breakdowns of these risks are looked in to. Statistical tests are used to validate research findings. All data were taken from hospital PFI full business cases, which I obtained from the individual hospital trusts under the Freedom of Information Act (30 November 2000). The main findings are that the 3.5% discount rate projects show a significantly lower proportional VFM than the 6% discount rate projects. The ranges of some of the test values are larger than would be expected from a controlled and standardised process. An example is the construction and development risk transferred as a proportion of all risk transferred in that project. This result ranges from 15.4% for the Queen Alexandra Hospital PFI project to 47.2% for the Lymington New Forest Hospital PFI project.